OPTIMASI PENJADWALAN PRODUKSI MENGGUNAKAN PERBANDINGAN METODE PALMER DAN NAWAZ ENSCORE & HAM (NEH) PADA PT. XYZ - Dani Wahyudi (2022)
A scheduling strategy can be said to be the most optimal solution if it has the smallest makespan value. PT XYZ is one of the manufacturers of automotive spare parts for motor vehicles. The problems experienced by PT. XYZ is a mismatch between the supply generated and demand from customers, as well as an unstable completion time in 2021 with a gap level of at most 7 minutes. Therefore, it is necessary to research on scheduling improvements in order to get a smaller makespan value so that the completion time will be smaller and can save production time as well as increase the amount of production. As a company that implements flowshop production flow, the algorithm that can be used in finding the best scheduling solution is to use classical heuristic methods such as the Palmer, Nawaz Enscore & Ham (NEH) and Campbell Dudek Smith (CDS) methods. Each method has a special iteration that is different from each other, so by processing data using these three methods, the smallest makespan result from the Nawaz Enscore & Ham (NEH) method with a value of 77 minutes with the job order J1-J2-J4-J3. The resulting dispatch list solution is able to minimize the completion time for the production of "Rear Bar New Reflector" by 4 minutes or 4.44% of the initial completion time.